The association of screen time with childhood obesity and metabolic status: a mediation analysis of cardiorespiratory fitness - Zhang, Jie; Wang, Bi-Lian; Jin, Han; Gu, Jia-Ying; Zhang, Jia-Hao; Shou, Guan-Fu; Wang, Hui; Zhang, Ping-Ping; Li, Li (Frontiers in Endocrinology, 2026)
BackgroundChildhood obesity and metabolic disorders are increasingly drawing global attention due to their long-term associations with chronic metabolic diseases. Excessive screen time is a key contributor to obesogenic behavior and is associated with unfavorable metabolic outcomes. This study aimed to analyze the relationships between screen time and obesity-related metabolic indicators in children and to explore the mediating role of cardiorespiratory fitness (CRF).MethodsBaseline data were drawn from the OptiChild study, involving 1,286 third-grade students in Ningbo, China. Anthropometric measurements, body composition, blood pressure, and fasting blood samples were collected. CRF was assessed using the 20-meter shuttle run test. Screen time, physical activity, and diet quality were assessed through questionnaires. Generalized linear mixed models were employed to analyze the associations, and mediation analysis was performed using bootstrap resampling.ResultsAfter adjusting for sex, age, maternal education level, physical activity and diet, higher screen time was significantly associated with increased visceral fat area (VFA) (β = 0.029, P = 0.009), body fat mass index (BFMI) (β = 0.109, P = 0.017), body fat percentage (BFP) (β = 0.469, P = 0.010), but decreased high-density lipoprotein cholesterol (HDL-C) (β = -0.014, P = 0.038). Mediation analysis indicated that CRF explained 66.6% of the association between screen time and VFA (P<0.05), 67.5% with BFMI (P = 0.014), 65.1% with BFP (P = 0.006), and 22.6% with HDL-C (P = 0.026).ConclusionIn Chinese children, lower screen time was associated with more favorable obesity-related profiles, with CRF playing as a significant mediator in this association.